1996
DOI: 10.1136/jech.50.6.674
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of data from proxy respondents in an international case-control study of cardiovascular disease and oral contraceptives. World Health Organization Collaborative Study of Cardiovascular Disease and Steroid Hormone Contraception.

Abstract: Study objectives -To evaluate the reliability of data supplied in a case-control study by proxy respondents for cases who were too ill to do so themselves. Design -A hospital based, case-control study of the current use of oral contraceptives (OC) and cardiovascular diseases. Data from "true" controls matched to a subset of cases were compared with those supplied by proxy respondents about the true controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
1
9
0
1
Order By: Relevance
“…However, given the remarkably strong agreement for all variables, and the consistency of our results with those previously reported for population surveys (Kolonel et al, 1977) and studies on cancer (Herrmann, 1985;Horwitz and Yu, 1985;Lerchen and Samet, 1986;Chong et al, 1989;Boyle and Brann, 1992;Johnson et al, 1993;Hamilton and Mack, 2000;Nadalin et al, 2003;Slanger et al, 2007), central nervous system disorders (Rocca et al, 1986;Chong et al, 1989;Wang et al, 1992;Villanueva and Garcia, 2006), and other diseases or exposures (Rogot and Reid, 1975;Thorogood and Vessey, 1989;Kelly et al, 1990;Velema et al, 1991;Nelson et al, 1994;Poulter et al, 1996;Phipps et al, 2000), it is more likely that both respondent types were a reliable sources for these demographic and life history variables.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, given the remarkably strong agreement for all variables, and the consistency of our results with those previously reported for population surveys (Kolonel et al, 1977) and studies on cancer (Herrmann, 1985;Horwitz and Yu, 1985;Lerchen and Samet, 1986;Chong et al, 1989;Boyle and Brann, 1992;Johnson et al, 1993;Hamilton and Mack, 2000;Nadalin et al, 2003;Slanger et al, 2007), central nervous system disorders (Rocca et al, 1986;Chong et al, 1989;Wang et al, 1992;Villanueva and Garcia, 2006), and other diseases or exposures (Rogot and Reid, 1975;Thorogood and Vessey, 1989;Kelly et al, 1990;Velema et al, 1991;Nelson et al, 1994;Poulter et al, 1996;Phipps et al, 2000), it is more likely that both respondent types were a reliable sources for these demographic and life history variables.…”
Section: Discussionsupporting
confidence: 84%
“…The ability of the study participant and next-of-kin to provide these data is of critical importance; validating these variables against an external record is often not possible; and, although they have generally been shown to be reliable (Rogot and Reid, 1975;Kolonel et al, 1977;Herrmann, 1985;Horwitz and Yu, 1985;Lerchen and Samet, 1986;Rocca et al, 1986;Chong et al, 1989;Thorogood and Vessey, 1989;Kelly et al, 1990;Nelson et al, 1990Nelson et al, , 1994Velema et al, 1991;Boyle and Brann, 1992;Wang et al, 1992;Johnson et al, 1993;Poulter et al, 1996;Hamilton and Mack, 2000;Phipps et al, 2000;Nadalin et al, 2003;Villanueva and Garcia, 2006;Slanger et al, 2007) and relatively complete (Kolonel et al, 1977;Pickle et al, 1983;Lerchen and Samet, 1986;Rocca et al, 1986;Nadalin et al, 2003;Campbell et al, 2007), conclusions may differ by survey instrument, population, or disease under study (Blot and McLaughlin, 1985;Nelson et al, 1990). Moreover, with one exception (Johnson et al, 1993), most studies to date have either reported on the reliability of proxy respondents in providing responses at the same time and setting as the study participant or compared the participants' own responses on two occasions over a short timespan.…”
Section: Introductionmentioning
confidence: 98%
“…47,48 For questions about use of health products and services (among which would be TCM products and services of TCM providers), studies have shown good agreement between proxy responses from family members and self-responses. [49][50][51] Individual-level variables. As shown in Figure 1, individuallevel variables were also entered into the analysis in order to determine whether they moderated variables within the patient's sociocultural context.…”
Section: Construction Of Variablesmentioning
confidence: 99%
“…Cases and controls were interviewed using a standardised questionnaire, if possible. If not (38% of cases), a close relative was interviewed; the information from these proxy interviews has been shown to be reliable [11]. …”
Section: Methodsmentioning
confidence: 99%